Ethnobotanical Assessment of Moringa oleifera Lam. in Southern Benin (West Africa) - Agoyi, Eric E.; Assogbadjo, Achille E.; Gouwakinnou, Gerard; Okou, Farris A.Y.; Sinsin, Brice (Ethnobotany Research and Applications, 2014)
<!–[if gte mso 9]> <![endif]–> For decades, plant species, particularly those used as non-tree forest products (NTFPs), have been known to play an important role in the livelihood of local populations, particularly in rural Africa. The present study investigated the uses of various parts of Moringa oleifera Lam. in southern Benin. It aimed at capturing indigenous knowledge on the uses of M. oleifera as a preliminary step toward future efforts to devise better management options of this plant species. An ethnobotanical survey was carried out in southern Benin (Guineo-Congolese zone) with a sample of 439 informants (201 women and 238 men) belonging to Fon, Waci, Xwla, Sahouè, Djerma, Kotafon, Aïzo, Goun, and Yoruba socio-cultural groups. It was found that M. oleifera is known in South Benin under different local names depending on the socio-cultural group. Leaves were the most used part followed by roots, bark, seeds, and pods. Leaves are eaten as a vegetable and also used for medicinal purposes. They are consumed fresh or dried and reduced to powder. Different parts of M. oleifera are used to treat up to 34 diseases according to the local populations. Leaves are also used as fodder for pigs, sheep, and rabbits. The seeds are used to carry out rites for blessing and attracting customers. The study showed that M. oleifera plays an important role in rural areas of South Benin where it is used as a nutritional and medicinal plant. Local populations could benefit by further adoption of the species in agroforestry systems. Depuis des décennies, les espèces végétales, particulièrement celles utilisées comme produits forestiers non ligneux (PFNLs) sont connues pour le rôle important qu’elles jouent dans la vie des populations locales. La présente étude a porté sur les utilisations faites des différentes parties de Moringa oleifera Lam. au Sud-Bénin. L’objectif de l’étude était de capitaliser les connaissances endogènes sur les utilisations de M. oleifera au Bénin afin de contribuer à une meilleure gestion de cette ressource. Il a été effectué une enquête ethnobotanique au Sud du Bénin (Zone Guinéo Congolaise) auprès d’un échantillon de 439 personnes (201 femmes et 238 hommes) appartenant aux ethnies Fon, Waci, Xwla, Sahouè, Djerma, Kotafon, Aïzo, Goun, Yoruba. L’enquête ethnobotanique a montré que M. oleifera est connu sous différentes appellations locales en fonction des groupes socio-culturels présents dans le sud Bénin. Les feuilles sont les organes les plus utilisés suivies des racines, l’écorce, les graines et gousses. Les feuilles sont utilisées fraîches comme légume-feuilles ou séchées et réduites en poudre. L’étude révèle que M. oleifera est utilisé dans le traitement de trente-quatre maladies selon les populations locales. Les feuilles sont aussi utilisées comme aliment dans l’élevage du porc, du lapin et de la volaille. Les graines sont utilisées pour faire des rituels dans le but d’attirer la clientèle ou le sexe opposé. Moringa oleifera joue un rôle très important pour les populations rurales du Sud-Bénin, surtout au plan nutritionnel et médicinal. Les populations locales devraient donc opter pour son intégration dans les systèmes agroforêstiers. <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–><!–[if gte mso 9]>